BOKO HARAM INSURGENCY AND VIOLENCE AGAINST WOMEN IN NORTH EASTERN NIGERIA - Mohammed Umar Bashir; Aisa Isa Geidam; Idris Mu’azu, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Violence against women generally has attracted the attention of many scholars globally. This study examines the violence against women perpetrated by the Boko Haram insurgency in the affected area of North Eastern Nigeria, where the Boko Haram insurgency is more predominant. For the purpose of this research convenient sampling was used to explore the experiences of women. A qualitative method of data collection was used. Both secondary and primary data was obtained through face to face individual interview where the original information was gathered from 18 victims of Boko Haram violence in Maiduguri, Borno state capital. The research discovered that the violence experienced by women in the affected areas is both physical and psychological. However, the physical violation has been more pronounced, as women are used for suicide bombings and are as well sexually abused. Many women went through sexual violence; the threat of being killed and later on serves as suicide bombers under Boko Haram insurgent’s custody. While some are still suffering from psychological trauma particularly those who witnessed the killings of either their children, spouses or other relatives. Furthermore, these women are mostly into small scale businesses in their homes such as knitting of caps, small poultry farms, animals fattening and etc but they were forced to abandon everything and ran for their lives. The study recommends psychosocial support to the victims and the provision of economic empowerment so as to enable the women to restart their businesses to give them a sense of belonging since most of them are business-oriented. This will help in making them adjust to new positive and favourable lives.